Creation of a Standard Model for Tube Feeding at Neonatal Intensive Care Unit Discharge. Issue 3 (24th September 2019) - White, Benjamin R.; Ermarth, Anna; Thomas, Debbie; Arguinchona, Olivia; Presson, Angela P.; Ling, Con Yee
Abstract: Background: Feeding dysfunction is a common consequence of prematurity and illness in neonates, often requiring supplemental nasogastric (NG) or gastrostomy (GT) feeding tubes. A standardized approach to the discharge of infants receiving home enteral nutrition (HEN) is currently lacking. Methods: The Home Enteral Feeding Transitions (HEFT) program was developed to identify patients eligible for HEN and create a standard discharge process. A structured tool helped determine discharge timing and route, and a dedicated outpatient clinic was created for infants discharged on HEN. Demographic, inpatient, and outpatient data were prospectively collected and compared with a historical cohort. Results: A total of 232 infants discharged from our neonatal intensive care unit (NICU) over 9 months met inclusion criteria. Ninety‐eight (42%) were discharged with HEN, 68 NG and 30 GT, compared with 134 (58%) receiving full oral feeds. This represented a 10% increase in HEN utilization ( P  = 0.003) compared with our historical control group. Median HEN length of stay was 31.5 days compared with our historical average of 41 days ( P  = 0.23). Frequency of emergency department visits and admissions because of HEN was unchanged postintervention. Parents were satisfied (8.6/10), and 98% said they would choose HEN again. The median time to NG discontinuation after discharge was 13.5 days, with an estimated cost savings of $2163 per NICU day. Conclusion: Our program is the first of which we know to use a standard care‐process model to guide the decision‐making and utilization of HEN at NICU discharge. HEFT shows that HEN at NICU discharge can be safe and effective, with high parental satisfaction.